Assessing Institutional Collaboration for Sustainable Watershed Management: A Case Study from Desa Rindu Hati, Bengkulu Tengah - Heru Purnawan; Henny Aprianty; Ocha Kauri; Deni Triyanto (Indonesian Journal Publisher, 2025)
This study evaluates institutional collaboration in managing the Bengkulu River Basin (DAS) as outlined in Regional Regulation Number 1 of 2017 on Watershed Management. A qualitative descriptive approach with a case study method was employed, focusing on key aspects of collaboration such as communication, decision-making coordination, conflict resolution, monitoring and evaluation, and procedural improvements. The goal of this research is to assess the steps taken to implement these collaborative elements.The findings indicate that leadership within the collaborating institutions plays a critical role in monitoring and evaluating watershed management efforts. However, despite these efforts, the integration of these institutions has not resulted in a unified approach. Each institution maintains its specific roles and functions, leading to fragmented implementation, even though the intention for collaboration exists. This study highlights both the challenges and opportunities in enhancing institutional collaboration for effective watershed management. It provides insights into how collaborative elements can be better realized to ensure a more integrated and efficient approach to managing the watershed, ultimately contributing to the success of watershed management initiatives. The research underscores the need for improved coordination, clearer roles, and more effective communication among the involved institutions to achieve a cohesive and sustainable management framework.